2012
DOI: 10.1111/j.1542-474x.2012.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Measure of the QT–RR Dynamic Coupling in Patients with the Long QT Syndrome

Abstract: Background The patients with the long QT syndrome type-1 (LQT-1) have an impaired adaptation of the QT interval to heart rate changes. Yet, the description of the dynamic QT/RR coupling in genotyped LQT-1 has never been thoroughly investigated. Method We propose a method to model the dynamic QT/RR coupling by defining a transfer function characterizing the relationship between a QT interval and its previous RR intervals measured from ambulatory Holter recordings. Three parameters are used to characterize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Our review also points out that it remains unknown if QT‐hys is a time invariant individual characteristic that could be lastingly impaired in response to aging and disease, or a marker of time‐varying and short‐lived conditions that are involved in the initiation of an arrhythmic event. While QT‐hys appears to be increased concurrently with exercise‐induced myocardial ischemia (Lauer et al., ; Zhang et al., ) or in the minutes preceding onset of torsades de pointes (Chen & Trayanova, ); QT‐hys from long ECG recordings (such as 24 hr Holter) is impaired in some conditions (Halamek et al., ; Malik et al., ; Pueyo et al., ), implying that QT‐hys could be durably altered. Condition‐specific studies using repeated or adaptive QT‐hys assessment from continuous ECG recordings would be beneficial to clarify this question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review also points out that it remains unknown if QT‐hys is a time invariant individual characteristic that could be lastingly impaired in response to aging and disease, or a marker of time‐varying and short‐lived conditions that are involved in the initiation of an arrhythmic event. While QT‐hys appears to be increased concurrently with exercise‐induced myocardial ischemia (Lauer et al., ; Zhang et al., ) or in the minutes preceding onset of torsades de pointes (Chen & Trayanova, ); QT‐hys from long ECG recordings (such as 24 hr Holter) is impaired in some conditions (Halamek et al., ; Malik et al., ; Pueyo et al., ), implying that QT‐hys could be durably altered. Condition‐specific studies using repeated or adaptive QT‐hys assessment from continuous ECG recordings would be beneficial to clarify this question.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, a single study investigated QT-hys in LQTS based on the estimation of the optimal RR memory in a dynamic QT/ RR model (Halamek et al, 2012). In a relatively large sample of LQT1 patients, they reported a significantly decreased QT-hys in LQT1 patients compared to controls, seemingly contradicting aforementioned studies which reported either increased QT-hys in ungenotyped LQTS samples (most likely including a significant proportion of LQT1 patients) (Chauhan et al, 2004;Gao et al, 2007;Krahn et al, 1997;Krahn et al, 2002) or similar QT-hys in LQT1 and controls (Chattha et al, 2010;Wong et al, 2010).…”
Section: Long Qt Syndromementioning
confidence: 99%
“…In the literature, other attempts have been made to quantify the dynamic QT-RR coupling 4,22,[36][37][38] . These approaches rely on statistical models of the given form and, thus, have assumptions behind the models.…”
Section: Discussionmentioning
confidence: 99%
“…Very little is known about the physiological background of repolarization and QT/RR coupling. It is well known that women have longer QTc and a steeper QT/RR slope compared to men [2][3][4], though the physiological explanation for such differences is not clear. These differences may be the result of genetic differences in the myocardium (heart properties, the distribution of action potentials) or genetic differences not originating in the heart (hormones, different concentration or distribution of ions).…”
Section: Introductionmentioning
confidence: 94%